An Analysis of Employee Views and The Effectiveness of Implementing Flexible Work Arrangements In Improving Work-Life Balance on Employees of Life Insurance Companies - Umi Rusilowati (Universitas Dharma Wacana, 2022)
The purpose of this research is to find out and analyze the views of employees, the factors that become obstacles, strategies that can be taken to overcome them, and the application of flexible work arrangements in improving work-life balance. The research method used in this research is descriptive qualitative. The data collection technique was done by triangulation (observation, interview, and documentation). The results of this study indicate that in general the experience of employees with flexible working hours is included in the positive category, respondents who undergo flexible work arrangements mostly experience additional working hours which can reach 10 to 12 hours